2005
DOI: 10.4314/sinet.v27i2.18243
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and survival of local and white leghorn chicken under intensive management system

Abstract: This study was conducted to evaluate the comparative growth, sexual maturity, survival, and feed utilization efficiency of local and White Leghorn chicken under intensive management condition. Five groups of each of the two breeds, with 200 baby chicks each, were subjected to appetite feeding with commercial layer's type starter's and grower's ration at day old to eight weeks and eight weeks to twenty weeks of age respectively in a completely randomised design with 5 replication. The results showed that mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
4
9
2
Order By: Relevance
“…The overall percentages loss or mortalities under intensive management reported in the current study was 42.2%. Mortality rate experienced in this study was comparable with what was reported in the study of Mopate and Lony [7] and little bit higher than those reported in previous studies of Pedersen, Demeke and Tadelle et al [8][9][10].…”
Section: Comparisons Of Observed Mortality Of Chickens Across the Thrsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall percentages loss or mortalities under intensive management reported in the current study was 42.2%. Mortality rate experienced in this study was comparable with what was reported in the study of Mopate and Lony [7] and little bit higher than those reported in previous studies of Pedersen, Demeke and Tadelle et al [8][9][10].…”
Section: Comparisons Of Observed Mortality Of Chickens Across the Thrsupporting
confidence: 91%
“…Other possible reasons for the high bird mortality observed in the current study could have been due to factors such as; chicks trauma to new environments, unfamiliar feeding situation, mixing of chicks from different households and different villages, a sudden isolation of chicks from their mother hence lack of motherly care during the early stages of the experiment. Similarly Demeke [9], reported that the reason for high mortality of local chickens under intensive management was not being familiar to confinement conditions. In contrast Tadelle and Ogle [11] gave possible reason for high mortality of local chickens under intensive management as disease problems and nutritional deficiencies which the authors found to be a serious problem in local chickens than in exotic stock.…”
Section: Comparisons Of Observed Mortality Of Chickens Across the Thrmentioning
confidence: 99%
“…The relative small feed cost and space requirement and the low price of the animals make chicken rearing a suitable farming activity for the rural poor. Unfortunately, despite the fact that more than 99% of the Ethiopian poultry production system consists of local chickens, traditionally considered to be disease resistant and adaptive to their environment, their contribution to human nutrition, gross domestic products and export earnings are disproportionately low (Demeke, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It contributed approximately 6.2% of the total livestock contribution of 2.67% to Agricultural Gross Domestic Product in 2012 and about 25% to the GDP of Nigeria in 2015 (CBN, 2012; PAN, 2015). Poultry plays an important economic, nutritional and socio-cultural role in the livelihood of poor rural households in many developing countries as they render not only economic services but also contribute significantly to human food as a primary supplier of meat, egg and raw materials to industries (feathers, waste products) as well as a source of income and employment to people, especially the most vulnerable rural households, compared to other domestic animals (Demeke, 2004). For instance, about 10% of Nigerian households are engaged in poultry production, mostly on subsistence and small or medium-sized farms.…”
Section: Introductionmentioning
confidence: 99%